"Everyone always did the same": Constructing legacies of collective industrial pasts in ex-mining communities in the South Wales Valleys. (November 2021) - Walker, Amy
Abstract: Understanding post-industrial places requires an engagement with how these communities construct identities around a sense of a shared or common industrial past, particularly in areas that have struggled to adapt to the loss of community-defining industries (Beatty et al. 2007). This paper draws on ethnographic data, non-directive interviews, and auto-ethnographic reflections collected in an ex-coal mining town in a South Wales valley in the UK. The paper seeks to better consider post-industrial collective identities by attending to concepts of collective memory and imaginaries of industrial pasts. Conceptualising memory as rooted in the material and immaterial; affective, emotive and discursive; shared and imagined; this paper discusses how everyday relationships are inextricably linked to an assumed shared history within an 'typical' active mining community. By engaging the everyday lives, practices, and discourses of contemporaneous residents this paper outlines the ways in which the past is constructed as universal and homogenous. It also extends this discussion to consider how these imagined shared pasts, and the enduring values routed in these collective memories, are mobilised to construct senses of inclusion, difference, and othering; imagined industrial pasts have enduring impacts for the construction of contemporary communities. Highlights: Industrial pasts are constructed as universal amongst residents, via discourses and practices. Industrial pasts are rooted in wider imaginaries of the typical 'coal-mining community'. Differences in experience are noted but overlooked for constructing collective identities. Values from industrial pasts are used 'other' residents who do nt appear to perform such values.